산림레포츠 활동특성에 따른 소비지출 분석 - 채진해; Jin-hae Chae; 김성학; Seong-hak Kim; 최낙민; Nak-min Choi (한국산림과학회지, 2024)
본 연구는 산림레포츠에 대한 관심과 수요가 확산되는 배경에서 산림레포츠 참가자의 소비지출 특성을 분석하고 활동특성에 따른 소비지출을 파악하는데 목적이 있다. 이를 위해 전국 성인 500명을 대상으로 설문조사를 실시하였으며, 동호회 가입 여부, 활동 시설유형에 따른 소비지출 차이를 분석하였다. 연구 결과, 산림레포츠 참가자의 1인당 연간 소비지출은 평균 1,846,000원으로 나타났으며, 소비지출 항목 중 동호회비가 가장 높은 비중을 차지했다. 선형 시설유형이 비선형 시설유형보다 소비지출이 4배 이상 높았으며, 동호회에 가입한 참가자는 비가입자에 비해 약 5배의 소비지출을 기록하였다. 이러한 결과는 산림레포츠 동호회의 활성화가 시장 확대에 중요한 역할을 할 수 있음을 시사한다. 또한, 산림레포츠의 활성화를 위해서는 기존 임도 및 숲길을 활용한 선형 활동과 관련된 시설 투자가 필요하며, 이를 통해 지역경제의 직접적·간접적 활성화가 가능하다는 점을 확인하였다. There is a growing interest and demand for forest-based leisure and sports activities. This study analyzed the expenditure patterns of individuals participating in such activities and examined how these expenditures vary based on the activity. A survey of 500 adults across South Korea was conducted, analyzing differences in expenditure according to membership in clubs and the type of activity facility (linear vs. nonlinear). The average annual expenditure per participant was 1,846,000 KRW, with club membership fees accounting for the largest proportion. Linear facility types showed expenditures over four times higher than those of nonlinear types, and club members spent about five times more than nonmembers. These findings suggest that the promotion of forest leisure sports clubs can play a crucial role in market expansion. Additionally, this study highlights the need for investing in facilities supporting linear activities, such as existing forest roads and trails, which could directly and indirectly contribute to local economic revitalization.